The Antarctic ozone hole during 2014 - Krummel, PB; Andrew Klekociuk; Tully, MB; Gies, HP; Simon Alexander; Fraser, PJ; Henderson, SI; Schofield, R; Shanklin, JD; Stone, KA (2020)
We review the 2014 Antarctic ozone hole, making use of a variety of groundbased and space-based measurements of ozone and ultra-violet radiation, supplemented by meteorological reanalyses. While the polar vortex was relatively stable in 2014 and persisted some weeks longer into November than was the case in 2012 or 2013, the vortex temperature was close to the long-term mean in September and October with modest warming events occurring in both months, preventing severe depletion from taking place. Of the seven metrics reported here, all were close to their respective median values of the 1979-2014 record, being ranked between 16th and 21st of the 35 years for which adequate satellite observations exist.